Analisis Strategi Bisnis Pada Pt. Xyz - Felicia Verdiana Wibisono (Universitas Tarumanagara, 2019)
In past few years, Indonesian people have a lot of interest in traveling and other outdoor activities like hiking, camping, etc. People start to explore the beauty of Indonesia and it impacts to the increase in Indonesia tourism. This condition makes many people looking for stuffs to support their outdoor activities. This increasing demand stimulates many local companies produce outdoor gear and this market facing a tighter competition than before. The purpose of this research is to analyze the proper strategy for PT. XYZ in facing the market competition. Defining internal and external factors of the company are important in formulating the alternative strategies. Therefore, this research use descriptive qualitative method and using CPM Matrix, IFE Matrix, EFE Matrix, SWOT Matrix, IE Matrix, and QSPM to find out the suitable strategy which will help the company survive in market competition. In final result, the suitable strategy for PT. XYZ is developing the waterproof product (shoes and carrier) for tropical product.